Evaluating the Effect of Cultivars and Seeding Rates on the Yield of Lentil Grown under the Vertisols Production System - Mebrate Tamrat Woldeselassie; Abel Gizaw; Simegnew Aniley (Advances in Agriculture)
Lentil is the second leading pulse crop grown in the central highland Vertisols of Ethiopia. However, waterlogging and the lack of situation-specific seed rate recommendations are among the problems that constrain its productivity. Therefore, a field experiment was conducted during 2017 and 2018 to determine the economically optimum seed rate for broadcast sowing of lentil varieties on Vertisols of North Shewa. Factorial combinations of two varieties of lentils (“Derash,” large-seeded and “Local cultivar,” small-seeded) and six seed rates (40, 60, 80, 100, 120, and 140 kg/ha) were tested in RCBD. According to the ANOVA results, the main effects of the environment, variety, and seed rate showed a significant effect on most parameters considered, except hundred seed weight for the environment, the number of seeds per pod for variety and plant height, and hundred seed weight for the main effect of seed rate. Lower yields were obtained in the second year due to the occurrence of sporadic unidentified disease, which might have created a confounding effect with variations due to the environment. The grain yield of variety “Derash” was best fitted to a power function, whereas “Local cultivar” showed a quadratic response with increasing seed rates ranging from 40 to 140 kg/ha. There was a positive and significant p<0.001 correlation between grain yield and each of the following: plant height, number of pods per plant, number of seeds per pod, and 100-seed weight. Based on ANOVA and economic analysis results, a seed rate of 100 kg/ha was found to be optimum for both varieties under the broad bed and furrow production systems on Vertisols.